Successful sequential therapy with rituximab and telitacicept in refractory Anti-NMDA receptor encephalitis and MOG-associated demyelination: a case report and literature review - Jingliang Zhang; Minzhe Hu; Chunjuan Wang; Shougang Guo (Frontiers in Immunology)
Clinical management of the rare and complex overlapping syndrome of MOG-antibody disease and anti-NMDAR encephalitis (MNOS), which has an uncertain pathogenesis and a high risk of recurrence, is highly challenging. We describe the case of a 19 years-old female patient, who first complained of headache, fever, and irritability. After that, she experienced frequent seizures and mood disorders. The diagnosis of MNOS was verified through antibody tests and imaging. For the patient, intravenous immunoglobulin and high-dose methylprednisolone were effective as first-line immunotherapy. Long-term immunotherapy with oral prednisone and mycophenolate mofetil was used to prevent relapses. However, over six years, the patient had five relapses when the mycophenolate mofetil dosage was reduced. The patient’s condition stabilized after taking rituximab as second-line immunotherapy, with less than 1% of total lymphocytes being CD19+ cells. Eleven months later, the plasmablast ratio increased, and patients experienced new symptoms such as bilateral optic neuritis. After that, the patient got telitacicept injections regularly for 13 months, during which time her symptoms subsided, and there were no adverse effects or relapses. This case suggests that telitacicept may be a viable adjunct or sequential therapy option for the depletion of B cells in MNOS.